1990
DOI: 10.1254/jjp.54.447
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulating Activity of Ginsenoside Rg1 from Panax Ginseng

Abstract: Abstract-The immunomodulatory activity of ginsenoside Rg1 from Panax ginseng was studied in mice using sheep red cells as the antigen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(89 citation statements)
references
References 11 publications
(4 reference statements)
1
86
0
2
Order By: Relevance
“…Ginsenosides have been shown to have a wide variety of biological activities including immunomodulatory effects, antioxidant, anti-inflammatory and anti-tumor activity (Kenarova et al, 1990;Attele et al, 1999;Shibata 2001;Park et al, 2003). A series of studies have demonstrated that Ginsenoside Rb1 effectively protects against cerebral, heart and lung ischemia/reperfusion injuries (Zeng et al, 2003;Geng et al, 2005;Li et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginsenosides have been shown to have a wide variety of biological activities including immunomodulatory effects, antioxidant, anti-inflammatory and anti-tumor activity (Kenarova et al, 1990;Attele et al, 1999;Shibata 2001;Park et al, 2003). A series of studies have demonstrated that Ginsenoside Rb1 effectively protects against cerebral, heart and lung ischemia/reperfusion injuries (Zeng et al, 2003;Geng et al, 2005;Li et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenosides, which are glycosides containing an aglycone (protopanaxadiol or protopanaxatriol) with a dammarane skeleton, are the major effective components of ginseng and have been shown to have a wide variety of biological activities including immunomodulatory effects, antioxidant, anti-inflammatory and anti-tumor activity (Kenarova et al, 1990;Attele et al, 1999;Shibata, 2001;Park et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenoside Rh1 and Rh2 have recently been reported to cause differentiation of F9 teratocarcinoma cells, and it has been suggested that the effects of ginsenosides might have been exerted via binding with a glucocorticoid receptor or its analogous nuclear receptor (60). In nude mice bearing HRA cell tumors, oral administration of Rh2 resulted in a significant retardation of tumor growth, consequently markedly prolonging survival time (58).…”
Section: Identification Of Active Anticarcino-genic Components In Redmentioning
confidence: 99%
“…Recently, intensive biochemical and molecular studies have shown pharmacological effects of ginseng in the central nervous system and cardiovascular, endocrine, and immune systems as well as in cases of cancer [8][9][10][11][12]. These studies suggest that the preventive effects of ginseng are due to its antiinflammation, anti-oxidation, and cytoprotective activities [13][14].…”
Section: Introductionmentioning
confidence: 99%